Analysis of the Pattern Shapes Obtained By Micro/Nanospherical Lens Photolithography - Yu, Guoxu (Langmuir : the ACS journal of surfaces and colloids, 2023)
Micro/nanospherical lens photolithography (SLPL) constitutes an efficient and precise micro/nanofabrication methodology. It offers advantages over traditional nanolithography approaches, such as cost-effectiveness and ease of implementation. By using micrometer-sized microspheres, SLPL enables the preparation of subwavelength scale features. This technique has gained attention due to its potential applications. However, the SLPL process has a notable limitation in that it mostly produces simple pattern shapes, mainly consisting of circular arrays. There has been a lack of theoretical analysis regarding the possible shapes that can be created. In our experiments, we successfully prepared annular and ring-with-hole pattern shapes. To address this limitation, we applied the Mie scattering theory to systematically analyze and summarize the various patterns that can be obtained through the SLPL process. We also proposed methods to predict and obtain different patterns. This theoretical analysis enhances the understanding of SLPL and expands its potential applications, making it a valuable area for further research